Treatment of Iron Deficiency Anemia in Pregnancy with Intravenous versus Oral Iron: Systematic Review and Meta-Analysis - Govindappagari, Shravya; Burwick, Richard M. (American Journal of Perinatology, 2019)
Objective To perform a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the benefits of intravenous (IV) iron in pregnancy.Study Design Systematic review was registered with PROSPERO and performed using PRISMA guidelines. PubMed, MEDLINE, Web of Science, ClinicalTrials.gov, Cochrane Library, and Google Scholar were searched. Eleven RCTs, comparing IV to oral iron for treatment of iron-deficiency anemia in pregnancy, were included. Meta-analyses were performed with Stata software (College Station, TX), utilizing random effects model and method of DerSimonian and Laird. Outcomes were assessed by pooled odds ratios (OR) or pooled weighted mean difference (WMD). Sensitivity analyses were performed for heterogeneity.Results We found that pregnant women receiving IV iron, compared with oral iron, had the following benefits: (1) Achieved target hemoglobin more often, pooled OR 2.66 (95% confidence interval [CI]: 1.71–4.15), p < 0.001; (2) Increased hemoglobin level after 4 weeks, pooled WMD 0.84 g/dL (95% CI: 0.59–1.09), p < 0.001; (3) Decreased adverse reactions, pooled OR 0.35 (95% CI: 0.18–0.67), p = 0.001. Results were unchanged following sensitivity analyses.Conclusion In this meta-analysis, IV iron is superior to oral iron for treatment of iron-deficiency anemia in pregnancy. Women receiving IV iron more often achieve desired hemoglobin targets, faster and with fewer side effects.
Keywords: anemia; pregnancy; iron deficiency; oral iron; intravenous iron